COMPARISON OF THE EFFECTIVENESS OF HORMONAL AND NON-HORMONAL METHODS OF TREATMENT OF EARLY MANIFESTATIONS OF CLIMACTERIC SYNDROME - Радзинский, Виктор Евсеевич; Костромина, Анна Андреевна (Mother and Baby in Kuzbass, 2017)
Early manifestations of climacteric syndrome (hot flashes, night sweats, depression, and others) are widespreadin middle-aged women. Hot flashes , in particular, dramatically reduce the quality of life of these women, which in many cases requires treatment. Selection of individual adequate and affordable therapy is one of the main issues of modern gynecology. The aim of the study was to evaluate the effectiveness of different hormonal and non-hormonal methods of managing of of climacteric syndrome’s early manifestations. Materials and methods. Dynamic evaluation of the severity of manifestations using the Green questionnaire in various drug groups, a comparative prospective placebo-controlled study. Results. The most effectivemedicine intreating of all manifestations of menopausal syndrome are preparations of menopausal hormone therapy. Serotonin uptake inhibitors are effective in treating vasomotor and emotional symptoms. Phytoestrogens and dietary supplements are less effective. Conclusion. Individual therapy, taking into account the impact on the main syndromes is a promising direction of research.